Providers' knowledge of, attitude to and practice of emergency contraception - UZUNER, ARZU; AKMAN, MEHMET; ÇİFÇİLİ, SALİHA SERAP (PARTHENON PUBLISHING GROUP, 2005)
Objectives Barriers to widespread use of hormonal emergency contraceptives (EC), such as lack of knowledge and prejudices held by health-care providers, still exist today. This study was initiated to evaluate the knowledge, attitudes and prejudices of family-planning (FP) providers. Methods This survey was conducted in FP units of primary-health-care centers in Istanbul. A total of 180 providers were interviewed in 80 units to whom a questionnaire was administered by face-to-face technique. Results One-hundred and fifty-two of the providers stated that they had heard of EC. The correct timing and dose interval of EC were known by 50% of them. The participants held the belief that EC caused abortion (39.4%), and that it was harmful for the fetus (31.1%). Other prejudices were the possibility of increased unprotected sexual intercourse (78.9%) and a tendency for men to give up condom use (75%); female providers were more prejudiced concerning these statements. The providers' tendency towards the provision of counseling was significantly related to their prejudices (p = 0.01, 1, p = 0.033) and to the application rate (P = 0.000). Conclusion Providers need more detailed information about EC. During FP training courses, the providers should be encouraged towards counseling EC which would increase the application rate of the users and decrease their own prejudices.
Keywords: emergency contraception; knowledge; hormonal contraceptives; provider; prejudice; POSTCOITAL CONTRACEPTION; PEDIATRICIANS KNOWLEDGE; KENYA; PROVISION; STUDENTS; NAIROBI